1999
DOI: 10.1074/jbc.274.26.18374
|View full text |Cite
|
Sign up to set email alerts
|

Cation Selectivity of Gastric H,K-ATPase and Na,K-ATPase Chimeras

Abstract: Chimeras of the catalytic subunits of the gastric H,KATPase and Na,K-ATPase were constructed and expressed in LLC-PK 1 cells. The chimeras included the following: (i) a control, H85N (the first 85 residues comprising the cytoplasmic N terminus of Na,K-ATPase replaced by the analogous region of H,K-ATPase); (ii) H85N/H356 -519N (the N-terminal half of the cytoplasmic M4 -M5 loop also replaced); and (iii) H519N (the entire front half replaced). The latter two replacements confer a decrease in apparent affinity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 30 publications
3
25
1
Order By: Relevance
“…Indeed, many reports demonstrate that regions outside the proposed occlusion pocket influence the cation selectivity (31)(32)(33)(34). In the present study we shed some light on the regions involved in the cation specificity of Na ϩ ,K ϩ -ATPase and H ϩ ,K ϩ -ATPase.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Indeed, many reports demonstrate that regions outside the proposed occlusion pocket influence the cation selectivity (31)(32)(33)(34). In the present study we shed some light on the regions involved in the cation specificity of Na ϩ ,K ϩ -ATPase and H ϩ ,K ϩ -ATPase.…”
Section: Discussionmentioning
confidence: 77%
“…In the past decade, it has been demonstrated that the predicted transmembrane segments 4 -6 are involved in cation occlusion (35). Recently, Mense et al (34) (33) suggested that both the N-terminal half of the intracellular M4-M5 loop and the adjacent transmembrane helice(s) of Na ϩ ,K ϩ -ATPase and H ϩ ,K ϩ -ATPase play a role in cation selectivity. Chimera HN16 includes all these fragments, except Val 898 -Ile 953 .…”
mentioning
confidence: 99%
“…This lysine substitutes for a serine present in the Na,K ATPase isoforms. Site-directed mutagenesis of residues of the Na,K ATPases [36,37], the SR Ca ATPase [38] and the H,K ATPase [27,35,39] showed that the ion-binding domain and other features of the gastric ATPase were similar to the Na,K and SERCA Ca ATPases.…”
Section: Secondary Structurementioning
confidence: 99%
“…As proposed by James et al (28) The T345A replacement likely decreases apparent K ϩ affinity by directly affecting the cation binding pocket. Although the cation binding sites of the sodium pump are located within the transmembrane segments, earlier studies, such as our H,K/ Na,K-ATPase chimera experiments, showed that a portion of the M4-M5 loop juxtaposed to the stalk segment leading to M4-affected cation selectivity (29). Furthermore, based on the alignment of the amino acid sequence of the Na,K-ATPase with the homologous sarco(endo)plasmic reticulum Ca 2ϩ -ATPase pump and with a known crystal structure, Thr-345 is located in stalk segment 4 within three residues of the plasma membrane (30,31), at least in the E 1 conformational state.…”
Section: Figmentioning
confidence: 99%